Immunotherapy in anaplastic thyroid cancer: Case series - Shyang-Rong Shih (Journal of the Formosan Medical Association, 2022)
Unresectable anaplastic thyroid cancer (ATC) has a poor prognosis. Chemotherapy and radiotherapy have limited effects on it. Here, we present four cases who underwent immunotherapy for ATC. The patients were aged between 58 and 70 years. Two male patients with pulmonary metastases received pembrolizumab and lenvatinib. However, they died of septic shock and respiratory failure in 2.7 and 1 months, respectively, after the initiation of combination therapy. Another male patient with stage IVB disease was treated with spartalizumab. The tumor remained stable after surgical debulking but slightly progressed after 23 months. He survived for 45.5 months after spartalizumab initiation. A female patient with BRAF-mutant ATC and lung metastases was treated with a combination of pembrolizumab and lenvatinib, which was complicated with grade 4 transaminitis. The patient subsequently received dabrafenib (a BRAF inhibitor) and trametinib (a MEK inhibitor) treatment, which was continued for 10.2 months with a best response of partial remission. She died 18 months after the initial diagnosis (11.4 months after treatment with dabrafenib and trametinib). In conclusion, the treatment responses of immunotherapy, either alone or in combination with other therapies, were highly variable in patients with ATC and should be carefully monitored along with the side effects.